Respuesta :

Answer:

y =x² + y² + 2y - 35

Step-by-step explanation:

The equation of a circle is given by the formula;

(x-a)²+(x-b)² = r²

Where;  (a, b) is the center of the circle and r is the radius

Therefore;

(x-0)² +(y+1) = 6²

x²+ y² +2y + 1= 36

x² + y² + 2y - 35 = 0

Therefore; The equation of the circle is y = x² + y² + 2y - 35

Answer:

x²+(y+1)²  = 36

Step-by-step explanation:

We have given that

Center  = (0,-1)  ; Radius = 6

We have to find the equation of circle.

The equation of circle is :

(x-h)²+(y-k)²  = r² where (h,k) is the center of circle and r is the radius.

(h,k) =(0,-1) and r  = 6

Putting values in above equation, we have

(x-0)²+(y-(-1))² = (6)²

(x)²+(y+1)² = 36

x²+(y+1)²  = 36 which is equation of circle.